Molecular Modeling Approach for the Discovery of Escherichia coli O157:H7 Interaction Inhibitors of Natural Product Compounds - Pitchuanchom, S.; Nontakitticharoen, M.; Thaisuchat, H. (Asian Journal of Chemistry, 2019)
The aim of this study is to report the development of Escherichia coli O157:H7 template for structure-based drug design. This template was validated by redocking with crystal ligand I. The results showed a good matching of docked and the crystallographic binding orientations with root mean square deviation (RMSD) less than 2.0 Å. Moreover, the developed template was applied to predict binding mode of 19 known E. coli inhibitors and 40 natural products. The results showed that the binding energy of almost E. coli inhibitors was related to their biological activity. The use of developed E. coli O157:H7 template in automated docking could speed up the process of novel drug discovery by allowing designed inhibitors to be tested computationally before the compounds are synthesized.